Disinfection Performance of a Drinking Water Bottle System With a UV Subtype C LED Cap Against Waterborne Pathogens and Heterotrophic Contaminants - Mariita, Richard M.; Blumenstein, Sébastien A.; Beckert, Christian M.; Gombas, Thomas; Randive, Rajul V. (Frontiers in Microbiology, 2021)
The purgaty One systems (cap+bottle) are portable stainless-steel water bottles with UV subtype C (UVC) disinfection capability. This study examines the bottle design, verifies disinfection performance against Escherichia coli, Pseudomonas aeruginosa, Vibrio cholerae, and heterotrophic contaminants, and addresses the public health relevance of heterotrophic bacteria. Bottles were inoculated with deliberately contaminated potable water and disinfection efficacy examined using colony forming unit (CFU) assay for each bacterial strain. The heterotrophic plate count (HPC) method was used to determine the disinfection performance against environmental contaminants at day 0 and after 3days of water in stationary condition without prior UVC exposure. All UVC irradiation experiments were performed under stationary conditions to confirm that the preset application cycle of 55s offers the desired disinfection performance under-tested conditions. To determine effectiveness of purgaty One systems (cap+bottle) in disinfection, inactivation efficacy or log reduction value (LRV) was determined using bacteria concentration between UVC ON condition and controls (UVC OFF). The study utilized the 16S ribosomal RNA (rRNA) gene for characterization of isolates by identifying HPC bacteria to confirm if they belong to groups that are of public health concern. Purgaty One systems fitted with Klaran UVC LEDs achieved 99.99% inactivation (LRV4) efficacy against E. coli and 99.9% inactivation (LRV3) against P. aeruginosa, V. cholerae, and heterotrophic contaminants. Based on the 16S rRNA gene analyses, the study determined that the identified HPC isolates from UVC irradiated water are of rare public health concern. The bottles satisfactorily inactivated the target pathogenic bacteria and HPC contaminants even after 3days of water in stationary condition.